2000
DOI: 10.1093/ajcn/71.5.1077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding 4 levels of soy protein for 3 and 6 wk on blood lipids and apolipoproteins in moderately hypercholesterolemic men

Abstract: Our findings show that consuming as little as 20 g soy protein/d instead of animal protein for 6 wk reduces concentrations of non-HDL cholesterol and apo B by approximately 2.6% and 2.2%, respectively. 2000;71:-84.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
68
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(86 citation statements)
references
References 18 publications
14
68
3
Order By: Relevance
“…Further, there is large variability in response to soy as shown in the meta-analysis, since about half of the 31 studies analysed by Anderson et al (1995) showed only minimal LDL-C lowering for reasons that have not been resolved. Among recent well-designed and executed trials, the reduction in non-high-density lipoprotein cholesterol (HDL-C) has been as low as 2.6% (Teixeira et al, 2000) or that of LDL-C no greater than with the milk protein-based control diets (Teede et al, 2001;Meinertz et al, 2002). As is seen with other cholesterol-lowering nutritional interventions, the best responses to soy protein were shown by individuals with the highest initial LDL-C levels (Crouse et al, 1999;Vigna et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is large variability in response to soy as shown in the meta-analysis, since about half of the 31 studies analysed by Anderson et al (1995) showed only minimal LDL-C lowering for reasons that have not been resolved. Among recent well-designed and executed trials, the reduction in non-high-density lipoprotein cholesterol (HDL-C) has been as low as 2.6% (Teixeira et al, 2000) or that of LDL-C no greater than with the milk protein-based control diets (Teede et al, 2001;Meinertz et al, 2002). As is seen with other cholesterol-lowering nutritional interventions, the best responses to soy protein were shown by individuals with the highest initial LDL-C levels (Crouse et al, 1999;Vigna et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of soy proteins in place of animal proteins can significantly lower plasma LDL cholesterol and triglycerides without affecting HDL cholesterol (Anderson et al, 1995). Results from randomized controlled trials have shown that 20-50 g of soy proteins daily may significantly reduce LDL cholesterol in mildly hypercholesterolaemic individuals (Baum et al, 1998;Crouse et al, 1999;Teixeira et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Only four of the 19 RCTs reported a statistically significant effect of ISP on blood LDL (Hoie et al, 2005b;Radhakrishnan et al, 2009) or non-HDL (Baum et al, 1998;Teixeira et al, 2000) cholesterol concentrations. These studies considered a total of 309 subjects for data analyses (15-41 subjects per group) and provided 20 to 40 g of ISP per day for six to 24 weeks.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%
“…In eight of the 19 RCTs, background diet was not assessed and possible confounding effects resulting from differences in background diet between the intervention and the control were not taken into account. Dietary intake was assessed in the remaining 11 studies, either by food frequency questionnaires (Allen et al, 2007;Crouse et al, 1999;Kreijkamp-Kaspers et al, 2004;Thorp et al, 2008) or by three-day dietary records (Baum et al, 1998;Greany et al, 2004;McVeigh et al, 2006;Santo et al, 2008;Steinberg et al, 2003;Teixeira et al, 2000;Van Horn et al, 2001). …”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%
See 1 more Smart Citation